A note on the Gauss-Jacobi quadrature formulae for singular integral equations of the second kind - Ma, L; Korsunsky, A (2004)
A fast and efficient numerical method based on the Gauss-Jacobi quadrature is described that is suitable for solving Fredholm singular integral equations of the second kind that are frequently encountered in fracture and contact mechanics. Here we concentrate on the case when the unknown function is singular at both ends of the interval. Quadrature formulae involve fixed nodal points and provide exact results for polynomials of degree 2n-1, where n is the number of nodes. Finally, an application of the method to a plane problem involving complete contact is presented. © 2004 Kluwer Academic Publishers.